Measurement procedures for materials used in photovoltaic modules. Encapsulants. Measurement of optical transmittance and calculation of the solar-weighted photon transmittance, yellowness index, and UV cut-off wavelength Part 1-4, (4th December 2020) - British Standards Institution,
No abstract available